Understanding second language acquisition - Ellis, Rod (Oxford Oxford University press, 2015)
"In the 30 years since Rod Ellis first published the award-winning Understanding second language acquisition, it has become a classic text. This new, fully updated edition continues to provide an authoritative and highly readable introduction to key areas of theory and research in second language acquisition. Ellis presents a comprehensive overview of the different theories in this field and examines critical reactions to them. The book reflects recent trends in looking at cognitive and social aspects of second language acquisition, as well as examining the roles played by implicit and explicit instruction in language learning"--Page [4] of cover.
First edition published in 1985.
Includes a glossary of technical terms pertaining to the field of Second language acquisition (pages 313-327).
Includes bibliographical references (pages 329-353) and index.
Keywords: Second language acquisition